2022
DOI: 10.1158/1535-7163.mct-20-1025
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of Hepatocellular Carcinoma by GPC3-Targeted Bispecific Antibody and Irinotecan is Potent in Suppressing Tumor Growth in Mice

Abstract: Hepatocellular carcinoma (HCC) is a world leading cause of cancer-related mortality, and currently no curative treatment for advanced HCC is available. Glypican-3 (GPC3) is an attractive target for HCC immunotherapy. This study explored the efficacy of six GPC3-targeted bispecific antibodies, alone or in combination with chemotherapeutic drug Irinotecan, for the treatment of HCC. The bispecific antibodies were constructed using three different structures, knob-into-hole (KH), scFv-scFv-hFc, and scFv-hFc-scFv, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The choice of HEPG2 cells to assess the impact of gamma irradiation and paclitaxel on in vitro ADP-ribosyl transferase activity of PE24 moiety was based on the fact that HEPG2 cells are known for their high chemotherapeutic and radiotherapy resistance. Recent research was dedicated to generating ITs harnessing PE24 to combat chemo/radio-resistant HEPG2 cells (Chen et al 2022;Heiat et al 2021). For this reason, HEPG2 cells were used while exploring the impact of gamma radiation and paclitaxel on PE24 moiety.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of HEPG2 cells to assess the impact of gamma irradiation and paclitaxel on in vitro ADP-ribosyl transferase activity of PE24 moiety was based on the fact that HEPG2 cells are known for their high chemotherapeutic and radiotherapy resistance. Recent research was dedicated to generating ITs harnessing PE24 to combat chemo/radio-resistant HEPG2 cells (Chen et al 2022;Heiat et al 2021). For this reason, HEPG2 cells were used while exploring the impact of gamma radiation and paclitaxel on PE24 moiety.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the epitope may be more important than affinity. Similar studies on GPC3-targeted immunotherapy demonstrated that bispecific antibody that targets the C-terminal had stronger potency (35), while immunotoxins target the N-terminal of GPC3 had stronger potency (36).…”
Section: Discussionmentioning
confidence: 87%
“…The same group of potential targets mentioned above can again be considered in this case. Bispecific antibodies targeting GPC3 have shown activity in xenograft mice [84]. ERY974 is a bispecific antibody that engages CD3 on T cells and GPC3 on tumor cells that underwent a phase I trial in patients with any GPC3-positive solid tumor type.…”
Section: Bispecific Antibodiesmentioning
confidence: 99%